Perspektif Orangtua terhadap Anak Autisme dan Peranannya dalam Terapi (Studi Kasus PLA Provinsi Kepulauan Bangka Belitung) - Zonalisa Fhatri (Al-Mudarris, 2019)
The purpose of this study was to obtain a picture of the acceptance of parents of children with autism and their role in autism therapy. This research uses a qualitative approach. Characteristics of the study subjects included parents who had children diagnosed with autism. The number of subjects in this study were 4 people. Data collection techniques with interviews as the main method and observation as a supporting method. The interview results showed that overall all four subjects were able to fully accept the condition of their child who was diagnosed with autism. Acceptance is influenced by factors of support from extended families, including financial capacity, religious background, age, and support of experts and the general public. These four subjects are quite involved in handling their children ranging from ensuring the diagnosis of PLA doctors / psychologists, fostering communication with PLA therapists, providing honest information when consulting the development of their children, enriching knowledge, and assisting children when doing therapy.